KONVERSI SAMPAH ORGANIK DI LINGKUNGAN FMIPA UNIVERSITAS LAMPUNG MENJADI PUPUK ORGANIK CAIR (POC) DENGAN TEKNIK SOLUBLE LIQUID (SL) - Syaiful Bahri; John Hendri; Aspita Laila; Heri Satria; Yuli Ambarwati (Jurnal Abdi Insani, 2023)
One of the main problems faced by farmers in Lampung today is the limited or scarcity of subsidized fertilizers. Meanwhile, there is an interesting phenomenon that has occurred on campus, including at FMIPA, University of Lampung (Unila), that about waste. So far, organic waste in the Faculty of Mathematics and Natural Sciences, Unila, has not been utilized optimally. The organic waste is only collected and deposited at the Integrated Waste Management Site (TPST) at Unila to be sorted and then taken to the Final Disposal Site (TPA) of Bandar Lampung City. These conditions prompted us, as academics at the University of Lampung, to be moved to carry out a community service program with the theme "Conversion of organic waste in the Faculty of Mathematics and Natural Sciences at the University of Lampung into Liquid Organic Fertilizer (POC) using solid liquid (SL) techniques." This PKM activity aims to process organic waste into liquid organic fertilizer. The processing of organic waste into liquid organic fertilizer is carried out using the soluble liquid technique, in which the organic waste is chopped and then pressed using a press machine, the pressed liquid is added to the starter solution so that the solid particles can dissolve. The dregs resulting from the press are also added to the starter solution so that the dregs can be used as animal feed or compost. The resulting product is applied to plants around FMIPA Unila. The results of this PKM activity were in the form of 60 liters of liquid organic fertilizer (POC) from 100 kg of organic waste, in other words, a yield of 60% was obtained. The resulting POC was then applied to plants in the FMIPA environment. Apart from products in the form of POC, this activity was also able to slowly change the behavior of the Unila FMIPA academic community towards existing organic waste. It is hoped that regular coaching will change the FMIPA environment to be cleaner, healthier and greener. The liquid organic fertilizer produced can also be packaged to be further sold to farmers at affordable prices, so as to increase the economic value of organic waste which has not been utilized so far and also increase the income of some of the education staff in FMIPA Unila.